Perlindungan Konsumen dari Penyebarluasan Data Pribadi oleh Pihak Ketiga: Kasus Fintech Peer”To Peer Lending” - Veronica Novinna (University of Udayana, 2020)
Online loans are an instant method to get loans with technology basis and under control of the Financial Services Authority. Startups organizer have failed to protect consumers personal information thus creates problem in collecting debts.